Longhorn beetles fauna (Coleoptera: Cerambycidae) of Puszcza Pilicka - Kurzawa, Jacek (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
On the basis of the material collected from 1981-1995 in Pilica F orest and analysis of published data 76 species of Cerambycidae were recorded. Twenty nine of them have for the first time been recorded from the mentioned area.